Основи використання сучасних інформаційних технологій навчання у початковій школі - Остапйовська, Ірина Ігорівна; Ostapiovska, Iryna I. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті перераховано та обґрунтовано позитивні чинники впливу комп’ютерних технологій на формування особистості молодших школярів. Виділено аспекти застосування персонального комп’ютера (ПК) у навчально-виховному процесі. Охарактеризовано різні види прикладних програм, проаналізовано їх можливості та умови підвищення ефективності. Сформульовано критерії доцільності використання різних видів прикладних комп’ютерних програм для досягнення поставленої навчально-виховної мети у конкретному навчальному середовищі (колективі) та основні властивості цих занять. Окреслено коло проблем, які виникають під час застосування сучасних інформаційних технологій. The influence’s positive factors of using the computer by the younger pupils to form their personality are re-calculated and grounded in the article. The opportunities of increase the effectiveness of the educational process thanks to the using of modern information technology of studies (MITS) by the primary school teachers are actualyted. Four aspects of using the personal computer (PC) in the educational process such as: review the PC as the object of study, the formation certain skills of working with PC of the pupils, use a PC as a means of study, use the computers as a means of the development of the cognitive processes, – are selected. The different types of applied computers programs are characterized and identified conditions for their effective using. The criteria of using different types of application software to achieve the educational goals in a particular learning environment (collective) are formulated on the basis of research. The features of preparing the lessons with using MITS and basic properties of these ones are selected too. The possibilities of different types of application software in preparing and conducting lessons and extracurricular activities are analysed. The problems that arise when using MITS are defined.
Background to the use of modern information technology in primary school
Кафедра теорії і методики природничо-математичних дисциплін початкової освіти
Keywords: інформаційні технології навчання; технології навчання; сучасні інформаційні технології; інформаційні технології; Modern information technology of studies; educational technology; primary school; methodology